Towards sustainable and strategic management of water resources. (Regional development studies (Brussels, Belgium), 2000)
Summary: In the Mediterranean countries, water resources management is one of the key priority issues, not only because of the actual challenges of limited resources, but also because of the increasing stringent quality standards arising from European legislation. At the dawn of the 21st century, Mediterranean countries are now facing the challenge of securing both quantity and quality of water for future generations. In the context of the EU's Mediterranean regional development policy, the Institute for Prospective Technological Studies in cooperation with the Commission carried out this study which has a twofold objective: to provide Regional Policy DG with a tool for the evaluation of interventions in the domain of water resources management in the Mediterranean countries and to step up the work of European Spatial Development Perspective, one aspect of which is the sound management of water resources.